Penerapan Program Pengembangan Kewirausahaan Pada Mahasiswa (Tenant) di Universitas Kanjuruhan Malang - Alexius Endy Budianto; Eris Dianawati; Didik Iswahyudi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2019)
The implementation of the Entrepreneurship Development Program (PPK) at Kanjuruhan University in Malang is expected to achieve the objectives of: (1) creating start-ups and independent new entrepreneurs, (2) improving business management skills for industrial communities, (3) creating entrepreneurship training methods suitable for students , (4) business units that can generate profit as a source of generating revenue from Kanjuruhan Malang University, and (5) opening or providing employment. The stages in implementing PPK include: (1) Dissemination of the PPK program, this socialization is carried out through announcements on campus boards, campus websites, and social media (Student groups and Alumni Groups). (2) Participants register before they enter the PPK tenant. (3) Following a written test to see the scientific potential possessed about the world of entrepreneurship, followed by interviews to find out the motivation and seriousness of participants in the PPK program. (4) The results of the selection will determine 20 best value people as prospective tenants. (5) Participants must fill out the willingness sheet to complete the PPK  program to completion. Whereas specifically to be achieved are: soul growth and entrepreneurial culture on campus, increased ability to prepare business plans, development of products that have been produced by tenants after participating in PPK activities, the creation of innovative and renewable products. The program will be implemented in a participatory manner with knowledge transfer methods from the proposing team, business experts, UMKM players to PPK tenants through education and training, business simulations, internships, intensive assistance, preparing business plans, and applying business to the tenants' potential and talents.